Proteção em sistemas elétricos com geração distribuída utilizando a transformada wavelet - Paiva, Sâmara de Cavalcante (2015)
A typical electrical power system is characterized by centr alization of power gene- ration. However, with the restructuring of the electric sys tem, this topology is changing with the insertion of generators in parallel with the distri bution system (distributed gene- ration) that provides several benefits to be located near to e nergy consumers. Therefore, the integration of distributed generators, especially fro m renewable sources in the Brazi- lian system has been common every year. However, this new sys tem topology may result in new challenges in the field of the power system control, ope ration, and protection. One of the main problems related to the distributed generati on is the islanding formation, witch can result in safety risk to the people and to the power g rid. Among the several islanding protection techniques, passive techniques have low implementation cost and simplicity, requiring only voltage and current measuremen ts to detect system problems. This paper proposes a protection system based on the wavelet transform with overcur- rent and under/overvoltage functions as well as infomation of fault-induced transients in order to provide a fast detection and identification of fault s in the system. The propo- sed protection scheme was evaluated through simulation and experimental studies, with performance similar to the overcurrent and under/overvolt age conventional methods, but with the additional detection of the exact moment of the fault.